Study protocol for the OligoMetastatic Esophagogastric Cancer (OMEC) project: A multidisciplinary European consensus project on the definition and treatment for oligometastatic esophagogastric cancer. Issue 1 (January 2023) - Kroese, Tiuri E.; van Rossum, Peter S.N.; Nilsson, Magnus; Lordick, Florian; Smyth, Elizabeth C.; Rosati, Riccardo; Nafteux, Philippe; D'Ugo, Domenico; Chaudry, M. Asif; Polkowkski, Wojciech; Roviello, Franco; Gockel, Ines; et al.
Abstract: Background: A uniform definition and treatment for oligometastatic esophagogastric cancer is currently lacking. However, a comprehensive definition of oligometastatic esophagogastric cancer is necessary to initiate studies on local treatment strategies (e.g. metastasectomy or stereotactic radiotherapy) and new systemic therapy agents in this group of patients. For this purpose, the OligoMetastatic Esophagogastric Cancer (OMEC) project was established. The OMEC-project aims to develop a multidisciplinary European consensus statement on the definition, diagnosis, and treatment for oligometastatic esophagogastric cancer and provide a framework for prospective studies to improve outcomes of these patients. Methods: The OMEC-project consists of five studies, including 1) a systematic review on definitions and outcomes of oligometastatic esophagogastric cancer; 2) real-life clinical scenario discussions in multidisciplinary expert teams to determine the variation in the definition and treatment strategies; 3) Delphi consensus process through a starting meeting, two Delphi questionnaire rounds, and a consensus meeting; 4) publication of a multidisciplinary European consensus statement; and 5) a prospective clinical trial in patients with oligometastatic esophagogastric cancer. Discussion: The OMEC project aims to establish a multidisciplinary European consensus statement for oligometastatic esophagogastric cancer and aims to initiate a prospective clinical trial to improve outcomes for these patients. Recommendations from OMEC can be used to update the relevant guidelines on treatment for patients with (oligometastatic) esophagogastric cancer. Highlights: OligoMetastatic Esophagogastric Cancer (OMEC) project was established The OMEC project consists of five studies Recommendations from OMEC can be used to update the relevant guidelines OMEC aims to initiate a prospective trial to improve outcomes for these patients